Lacunae in the Uzbek language: Semantic and linguocultural dimensions - Usarov, Jabbor Eshbekovich; Axmadjonov, Doniyor Baxtiyor o’gli; Saidov, Ulmas Raxmatovich; Abdirimova, Intizor Kamilovna; Muratova, Nafisa Baxtiyarovna; Muxtorova, Shaxnoza Mashrabovna; Komilova, Gulmira Temirovna; Allayarova, Sojida Umirzakovna (Indonesian Journal of Applied Linguistics, 2026)
This study examines lacunae in the Uzbek language from semantic and linguoculturological perspectives, focusing on their role in encoding culturally specific meanings. Lacunae are defined as lexical, semantic, or conceptual gaps that occur when a linguistic unit in one language lacks a direct equivalent in another, often due to differences in cultural experience, cognitive categorization, or communicative practices. The study adopts a qualitative descriptive approach, drawing on data from Uzbek literary texts, lexicographic sources, and cross-linguistic comparisons to identify and analyze representative examples of lacunae. The findings indicate that the Uzbek language exhibits a wide range of lacunae, including subjective, communicative, textual, and cultural types. These lacunae reflect culturally embedded values, social relations, and conceptual structures that are integral to the Uzbek linguistic worldview. In translation contexts, such lacunae cannot be adequately rendered through direct lexical substitution and are typically addressed through descriptive translation, explication, or contextual reformulation. This resistance to simplification underscores the close relationship between linguistic form and cultural meaning. The study also clarifies the conceptual distinction between lacunae and realia, arguing that lacunae represent systemic absences within a linguistic or semantic framework, whereas realia refer to culturally specific objects or phenomena with established referential status. By addressing this distinction, the study contributes to terminological precision in lacunology and related fields. Overall, the research enhances understanding of the interaction between language and culture and offers insights relevant to translation studies, intercultural communication, and language documentation.